Successful Use of Epidural Anesthesia Following Guideline-Based Anticoagulation Bridging for Hip Surgery in a Patient with Acute Pulmonary Embolism: A Case Report - Ayudya Tarita Alda; Paramita Putri Hapsari; RTH Supraptomo (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2025)
Background: The perioperative management of patients with acute pulmonary embolism (PE) requiring major surgery presents a formidable clinical challenge. Therapeutic anticoagulation, essential for treating PE, is a significant relative contraindication for neuraxial anesthesia due to the risk of spinal hematoma. General anesthesia, however, carries a high risk of hemodynamic collapse in patients with compromised cardiopulmonary reserves. This report describes the successful application of a multidisciplinary, guideline-adherent strategy to manage this complex clinical scenario. Case presentation: A 56-year-old, obese female (BMI 30 kg/m²) with an extensive history of cardiovascular disease—including hypertensive heart disease, prior myocardial infarction, and an aortic dissection repaired via EVAR—presented with a post-traumatic left hip dislocation. Her presentation was critically complicated by an acute massive pulmonary embolism, diagnosed via echocardiography, which revealed large thrombi in the pulmonary arteries, and confirmed with a chest X-ray showing a Westermark sign. The patient required an open reduction and repair of the hip. A collaborative, multidisciplinary plan was formulated to enable the use of epidural anesthesia. Her anticoagulation with rivaroxaban was stopped five days preoperatively and bridged with a therapeutic infusion of unfractionated heparin (UFH). The UFH was discontinued six hours before the procedure, and surgery proceeded only after confirming normalization of coagulation parameters (INR < 1.5). Epidural anesthesia was successfully administered, providing excellent hemodynamic stability throughout the surgery. The patient was monitored in a cardiac intensive care unit postoperatively, with no neurological or bleeding complications. Conclusion: This case demonstrates that epidural anesthesia is a viable and potentially superior option for high-risk patients with acute PE, provided that a meticulous, guideline-concordant anticoagulation bridging strategy is implemented. Successful outcomes in such complex cases are predicated on rigorous multidisciplinary planning, patient selection, and vigilant postoperative monitoring. This approach validates current safety guidelines rather than challenging them, showcasing their utility in enabling advanced anesthetic care.